2020
DOI: 10.1371/journal.pone.0242539
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal factors affecting platelet parameters in late preterm and term neonates

Abstract: Platelets parameters including platelet count (PLT), plateletcrit (PCT), mean platelet volume (MPV) and platelet distribution width (PDW) are associated with various physiological and pathological functions in various disease. However, few studies have addressed whether perinatal factors may be associated with platelet parameters at birth in a large cohort of late preterm and term neonates. The aim of this study to investigate perinatal factors affecting platelet parameters in late preterm and term neonates. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Go et al has conducted a large cohort study that showed no differences in platelet volume parameters at birth between late-preterm and term neonates. 11 However, previous report by Alicja et al indicated that platelet count and plateletcrit were lower in late-preterm neonates compared with term neonates. 12 In our study, Regarding MPV, it was significantly higher in sepsis group than in control group (P-value <0.0001).…”
Section: Resultsmentioning
confidence: 90%
“…Go et al has conducted a large cohort study that showed no differences in platelet volume parameters at birth between late-preterm and term neonates. 11 However, previous report by Alicja et al indicated that platelet count and plateletcrit were lower in late-preterm neonates compared with term neonates. 12 In our study, Regarding MPV, it was significantly higher in sepsis group than in control group (P-value <0.0001).…”
Section: Resultsmentioning
confidence: 90%
“…In platelet-consuming diseases, the bone marrow compensates by enhancing megakaryopoiesis and releasing into the bloodstream larger and immature forms of platelets, leading to higher MPV and IPF values. 10 26 42 Several studies tested the IPF% values in thrombocytopenic neonates and detected low IPF% in IUGR neonates, 50 51 52 strengthening the assumption of hyporegenerative thrombocytopenia.…”
Section: Discussionmentioning
confidence: 97%
“…As a consequence of inadequate oxygenation, in utero blood flow to the liver is diminished affecting the liver's size and function, and thus also platelet production. 8,42,60 The hyporegenerative nature of IUGR thrombocytopenia is also underlined by the values of MPV and IPF. In plateletconsuming diseases, the bone marrow compensates by enhancing megakaryopoiesis and releasing into the bloodstream larger and immature forms of platelets, leading to higher MPV and IPF values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations